Inventarisasi Lalat Buah pada Cabai Rawit (Capsicum frustescens l.) di Desa Karya Maju Kecamatan Marabahan Kabupaten Barito Kuala - Syahri Rajab Al Rahmat; Elly Liestiany; Muhammad Indar Pramudi (www.ulm.ac.id, 2021)
One of the obstacles in the cultivation of cayenne pepper plants is the invasion of fruit flies. Yield reduction caused by fruit flies ranges from 50-75% moreover can reach 100% The aim of this research is to identify the species of fruit flies that attack cayenne pepper plantations. In this research, the total number of fruit flies caught was 2,786. Land 1 (1,352 individuals) and land 2 (1, 434 individuals). There were 4 species identified in the cayenne pepper field, namely Bactrocera dorsalis, B. papaya, B. carambolae, and B. umbrosa. B. dorsalis predominates in all these species. The highest number of species was B. dorsalis (858 individuals in field 1 and 866 individuals in land 2), B. papayae (368 individuals in field 1 and 393 individuals in land 2). B. carambolae (117 individuals in land 1 and 171 individuals in land 2). land 2), B. umbrosa (9 individuals in field 1 and 4 individuals in field 2).